Axle Counter Grounding System on The PPI Madiun Railway Using the Wenner Method - Sunardi; Akhwan; Adya Aghastya; Indra Budi Hermawan; Febry Pandu Wijaya; Daniar Fahmi (Journal of Railway Transportation and Technology, 2023)
Axle counter is a railway detection equipment producing wave frequencies to count the number of axles passing over the track. The existence of a mismatch between the initial and final count numbers usually leads to a red signal and this can prevent the formation of a travel route. The components of axle counter are often damaged by lightning strikes both directly and through the distribution of excessive currents due to a poor grounding system. However, these excessive currents can be safely grounded without damaging the components through the application of a good grounding system. Therefore, this research aimed to plan an effective grounding system to anticipate the incidents using the Wenner method. Some requirements such as soil type, depth, and electrode rod diameter were used in the process to determine the appropriate resistance value. The design was made based on the simulations that closely resembled real field conditions using Aspix software and grounding resistance values were also measured directly on the field to determine the discrepancies between the planning and actual conditions.